The third year of activities in the Nordic graduate school in mathematics education - Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2005)
The board of NoGSME had its first meeting of 2006 in Malmö, just before the Madif 5 research seminar, and planned the activities for 2006. Here we offer some first insights into the programme of 2006.